The Information Content of Specialist Pricing - Gould, John P.; Verrecchia, Robert E. (Journal of Political Economy, 1985)
This paper examines a process by which information-revealing prices are determined by considering the private incentives of a price-setting agent (whom we refer to as a specialist). The specialist has private information that may be (partially) revealed through his choice of a pricing rule. We define an equilibrium as a pricing rule and a response to that rule by a representative trader that maximizes the expected utilities of the specialist and the trader, conditional on each having rational expectations. By analyzing the existence and nature of this equilibrium, we attempt to develop further insights into the behavior of markets with incomplete information.